2005
DOI: 10.1055/s-2004-830431
|View full text |Cite
|
Sign up to set email alerts
|

Setup of Neurophysiological Monitoring with tcMEP/SSEP During Thoracoabdominal Aneurysm Repair

Abstract: TcMEP and SSEP allow an adequate, direct, and reliable intraoperative assessment of spinal cord function, enabling the surgeon to diagnose an impending ischaemia and act accordingly. This measurement technique provides the surgical team with a means of integrating neurological aspects during thoracoabdominal aneurysm repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The use of MEP and SSEP monitoring is timely, cost intensive, and demands adequate interpretation skills. 2,3 Postoperative management on the intensive care unit focuses mainly on (1) stabledsupranormaldmean arterial pressures and (2) a decrease of intrathecal pressure via a routinely placed CSF drainage to ensure adequate spinal perfusion via the collateral network despite lower postoperative perfusion pressures. 16 Monitoring of the spinal cord blood supply remains a difficult, but extremely important, in eliminating paraplegia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of MEP and SSEP monitoring is timely, cost intensive, and demands adequate interpretation skills. 2,3 Postoperative management on the intensive care unit focuses mainly on (1) stabledsupranormaldmean arterial pressures and (2) a decrease of intrathecal pressure via a routinely placed CSF drainage to ensure adequate spinal perfusion via the collateral network despite lower postoperative perfusion pressures. 16 Monitoring of the spinal cord blood supply remains a difficult, but extremely important, in eliminating paraplegia.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring of spinal cord function using motor evoked potentials (MEP) or somatosensory evoked potentials (SSEP) is widely accepted in the assessment of intraoperative spinal cord viability during aortic procedures, but it requires significant technical effort and invasiveness. 2,3 It has been shown that paraplegia may be reduced by sustaining a supranormal mean arterial pressure peri-operatively and by routine use of cerebral fluid (CSF) drainage. 4e7 Despite these and other strategies and technical improvements spinal cord ischemic injury remains significant with an incidence of 5e11% in contemporary series.…”
Section: Introductionmentioning
confidence: 99%
“…To monitor the spinal cord, we used the ISIS IOM-System (inomed Medizintechnik GmbH, Teningen, Germany) consisting of the ISIS-headbox and the OSIRIS-neurostimulator. We described the application of neurophysiological monitoring of the spinal cord previously [7]. Briefly, the needle electrodes for tcMEP stimulation were placed at C3/C4 according to the International 10-20 EEG-system, and those for tcMEP-recording at the tibialis anterior and gastrocnemius muscles (l " Fig.…”
Section: Neurophysiological Monitoringmentioning
confidence: 99%
“…(b) Postoperative CT-image (3D-reconstruction). Endoluminal implantation of two coated stent grafts and an additional iliac-hepatic bypass of the celiac axis.tcMEP stimulation electrodes are attached percutaneously to the C3/C4 region of the motor cortex, and SSEP recording electrodes are positioned at Cz/Fz 0[14]. TcMEP recording sites on the leg are located at the anterior tibial muscle and gastrocnemius muscle.…”
mentioning
confidence: 99%